2007
DOI: 10.1185/030079906x167426
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric comparison of three patient-based measures of asthma control

Abstract: The ACT and ACQ are comparable asthma control questionnaires. The choice of which questionnaire to use should be informed by considering several factors, such as the intended purpose and setting where the questionnaire will be used, as well as the content, practicality, availability of benchmark scores, and adaptability to multiple administration modes of each questionnaire. One potential limitation of the study is that the data were collected in a clinical setting with limited demographic information. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
2
20
0
1
Order By: Relevance
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
“…The area under the ROC curve, the single measure incorporating the most information on the relationship between ACT predicting GINA, was quite adequate at 0.84 and of a similar magnitude to prior findings for the ACT as well as other case identification instruments for asthma, allergy, and chronic obstructive pulmonary disease. [28][29][30] An ACT score >20 predicted GINA-defined controlled asthma 51% of the time, and the kappa statistic (0.42) suggested a moderate agreement using the cut-off point of >20 for 'well controlled' asthma. This is largely because substantial numbers of patients with an ACT score >20 had GINA 'partly controlled', and a few GINA 'uncontrolled', asthma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the working definition of the GINA criteria differed from that used in the present analysis as, in the earlier analysis, exacerbations experienced during the previous 12 months were included in the assessment of partly controlled asthma; exclusion of this criterion substantially improved the positive predictive value of an ACT score of o20. The ACT and ACQ have also been compared in a smaller population of patients, [20] and the authors concluded that these two measurement tools had comparable reliability, validity, accuracy and responsiveness.…”
Section: Discussionmentioning
confidence: 99%